Правовий режим воєнного стану: аналіз законодавства України - Синявська, О. Ю.; Syniavska, O. Yu.; Повалена, М. В.; Povalena, M. V.; Носевич, Н. Р.; Nosevych, N. R.; Олена Юхимівна Синявська (Академічні Візії. – 2023. – Вип. 17, 2023)
У статті досліджено питання правового режиму воєнного стану. Визначено поняття «воєнний стан», «надзвичайний стан» й «особливий період», а також спільні й відмінні риси між ними. Визначено, що передбачає введення воєнного стану. Розглянуто законні й підзаконні акти, які регулюють правовий режим воєнного стану. Розкрито роль Конституції в нормативній базі щодо правового режиму воєнного стану в Україні. Проаналізовано укази Президента щодо оголошення воєнного стану, мобілізації та продовження їх терміну, структуру цих указів. Узагальнено конституційні права і свободи людини і громадянина, які можуть обмежуватися і не можуть бути обмежені під час дії воєнного стану. Описано деталі формування та функціонування військових адміністрацій. Вивчено досвід запровадження воєнного стану в Україні. Зроблено висновки про необхідність змін у законодавстві щодо правового режиму воєнного стану й внесено пропозиції стосовно його вдосконалення.

The article examines the issue of the legal regime of martial law. The concepts of "martial law", "state of emergency" and "special period" are defined, as well as common and distinctive features between them. It was determined that martial law would be introduced. Legal and by-laws that regulate the legal regime of martial law are considered. The role of the Constitution in the regulatory framework regarding the legal regime of martial law in Ukraine is revealed. The Presidential Decrees regarding the declaration of martial law, mobilization and extension of their term, the structure of these decrees are analyzed. The process of introducing martial law is described. The constitutional rights and freedoms of a person and a citizen, which may or may not be limited during martial law, are summarized. The list of measures of the legal regime of martial law, which can be carried out, taking into account the limitations of the constitutional rights and freedoms of a person and a citizen, as well as the rights and legitimate interests of legal entities, is given. The details of the formation and functioning of military administrations are described. A list of activities that are categorically prohibited for the duration of martial law is provided. The experience of introducing martial law in Ukraine in 2018 as a result of the armed aggression of the Russian Federation in the area of the Kerch Strait and after the full-scale invasion of the Russian Federation into Ukraine in 2022 was studied. The activities of the Verkhovna Rada of Ukraine during martial law are indicated. The issue of adopting the draft Law "On the right to civilian firearms" was raised. Conclusions were made about the need for changes in the legislation regarding the legal regime of martial law and proposals were made for its improvement.

В статье исследованы вопросы правового режима военного положения. Определены понятия «военное положение», «чрезвычайное положение» и «особый период», а также общие и отличительные черты между ними. Определено, что предполагает введение военного положения. Рассмотрены законные и подзаконные акты, регулирующие правовой режим военного положения. Раскрыта роль Конституции в нормативной базе правового режима военного положения в Украине. Проанализированы указы Президента об объявлении военного положения, мобилизации и продлении их срока, структуре этих указов. Обобщены конституционные права и свободы человека и гражданина, которые могут ограничиваться и не могут быть ограничены во время военного положения. Описаны детали формирования и функционирования военных администраций. Изучен опыт введения военного положения в Украине. Сделаны выводы о необходимости изменений в законодательстве о правовом режиме военного положения и внесены предложения по его усовершенствованию.
Keywords: Адміністративне право та процес. Administrative Law and Procedure. Административное право и процесс; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; Державне адміністративне управління. Адміністративна діяльність. State Administration. Administrative Activity. Государственное административное управление. Административная деятельность; Держава і право. State and Law. Государство и право; legal regime; martial law; special period; Constitution; regulatory framework; law; cyber security; digitization; weapons; правовий режим; воєнний стан; особливий період; Конституція; нормативна база; закон; кібербезпека; цифровізація; зброя; правовой режим; военное положение; особый период; Конституция; нормативная база; кибербезопасность; цифровизация; оружие